Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 132640 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Alisma plantago-aquatica L." ] } The dataset includes 132640 records from 380 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000093-150805223722583/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences